A Comparative Study of Exceptional Experiences of Clients Seeking Advice and of Subjects in an Ordinary Population - Fach, Wolfgang; Atmanspacher, Harald; Landolt, Karin; Wyss, Thomas; Rössler, Wulf (Frontiers in Psychology, 2013)
Exceptional experiences (EE) occur frequently within the populations of many countries and across various sociocultural contexts. Although some EE show similarities with mental disorders, it would be a mistake to identify them in general as disorders. In fact, the vast number of individuals reporting EE includes subclinical and completely healthy subjects. We conducted a comparative empirical study of several characteristics of EE for two samples -- one from ordinary population and the other from clients seeking advice. We found surprisingly similar \Red{phenomenological patterns of EE in both samples, but} the frequency and intensity of EE for clients seeking advice significantly exceeded those for the ordinary population. Our results support the hypothesis of a continuous spectrum between mental health and mental disorder for the types of experiences analyzed.